2016
DOI: 10.1155/2016/2610873
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Short-Term Outcomes of HIV Patients Admitted to an African Intensive Care Unit

Abstract: Purpose. In high-income countries, improved survival has been documented among intensive care unit (ICU) patients infected with human immune deficiency virus (HIV). There are no data from low-income country ICUs. We sought to identify clinical characteristics and survival outcomes among HIV patients in a low-income country ICU. Materials and Methods. A retrospective cohort study of HIV infected patients admitted to a university teaching hospital ICU in Uganda. Medical records were reviewed. Primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
4
22
2
Order By: Relevance
“…Unlike the findings of other studies , HIV‐positive patients in this study who died in the ICU were significantly older than those who survived. Morris et al , for example, did not report any differences with regard to age, sex, race, ethnicity or HIV risk factors between survivors and nonsurvivors .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the findings of other studies , HIV‐positive patients in this study who died in the ICU were significantly older than those who survived. Morris et al , for example, did not report any differences with regard to age, sex, race, ethnicity or HIV risk factors between survivors and nonsurvivors .…”
Section: Discussioncontrasting
confidence: 99%
“…Morris et al , for example, did not report any differences with regard to age, sex, race, ethnicity or HIV risk factors between survivors and nonsurvivors . In keeping with the findings of Kwizera et al , the median length of ICU stay was marginally but statistically significantly longer in those who survived to discharge from the ICU. A plausible reason for this may be that HIV‐positive individuals who die in the ICU are more acutely ill upon ICU admission.…”
Section: Discussionmentioning
confidence: 59%
“…1) [2,3]. Such patients account for 10-30% of all ICU admissions of HIV-infected individuals, though this proportion appears dwindling over the past decade [4][5][6][7][8][9]. Of note, severely immunosuppressed Take-home messages Fig.…”
Section: The Current Landscape Of Hiv Infection In the Icumentioning
confidence: 99%
“…Lifetime low-level inflammation due to silent HIV replication in sanctuary sites, co-infections (e.g., CMV, EBV or HBV/HCV), intestinal dysbiosis, habitus (e.g., tobacco or intravenous drug use), sequelae of past infectious processes and long-term toxicity of certain antiretroviral medications may be implicated to varying degrees in the pathogenesis of these conditions [10,19,20]. Up to 70% of HIV-infected patients nowadays managed in the ICU are receiving long-term cART [6,8,9,[21][22][23][24]. This epidemiological shift translates into a continuous rise in non-AIDSrelated ICU admissions which broadly exceeded those for severe OIs in most of recent cohorts.…”
Section: The Current Landscape Of Hiv Infection In the Icumentioning
confidence: 99%
“…Both the relatively low rate of HIV infection [20] and the comparatively short duration between symptom onset and presentation to a healthcare facility may have further contributed to the low fatality rate. These observations may reflect the effectiveness of the Rwandese healthcare system and may explain why studies from other sub-Saharan African countries reported higher death rates in patients with acute infection and sepsis [20][21][22]. Our trial was therefore underpowered to detect a difference in hospital mortality.…”
Section: Discussionmentioning
confidence: 99%